BRYOPHYTE DIVERSITY AND ATMOSPHERIC POLLUTION IN A RESIDENTIAL AREA AND AN INDUSTRIAL URBAN FOREST IN JAKARTA, INDONESIA - Afiatry Putrika; Andi Salamah; Mega Atria; Dian Hendrayanti; Nurul Laksmi Winarni; Eliza Pricilia Purba; Sarah Tsabitudinillah; Nunik Sri Ariyanti (BIOTROPIA, 2023)
Bryophytes are nonvascular plants that have simple structures that are sensitive to environmental changes, and they can, therefore be used as indicators of air quality. The presence of bryophytes in disturbed urban ecosystems, such as residential and industrial areas, indicates that their structures have adapted to survive in such areas. The objective of this study was to compare the bryophyte diversity and air quality indices between a residential area and an industrial area in Jakarta. The research was conducted in the Bona Indah residential area in South Jakarta and the Jakarta Industrial Estate Pulogadung (JEIP) urban forest. Sampling was carried out using the transect method in the residential area and the quadratic method in the urban forest on three different substrates, namely rocks or concrete, soil and tree trunks. The percentage of the epiphytic bryophyte cover was measured using a 10 × 10 cm subplot. Voucher specimens were stored at the Herbarium UI DEP and Herbarium IPB. Twenty-one species of moss and three species of liverwort were found in the two locations. Bryophytes were found on all the substrates in the residential area, but in the urban forest, they were found only on tree trunks and rock/cement substrates. Based on the Shannon–Wiener Index, although both locations had moderate bryophyte diversity, the residential area’s bryophyte diversity was higher than that of the urban forest. The index of atmospheric purity in the residential area was 4.3, indicating a high level of pollution, and it was 0.3 in the urban forest, showing that it was also very polluted.